Restrictive spirometry pattern is associated with low physical activity levels. A population based international study. (January 2019) - Carsin, Anne-Elie; Fuertes, Elaine; Schaffner, Emmanuel; Jarvis, Debbie; Antó, Josep M.; Heinrich, Joachim; Bellisario, Valeria; Svanes, Cecilie; Keidel, Dirk; Imboden, Medea; Weyler, Joost; Nowak, Dennis; et al.
Abstract: Introduction: Restrictive spirometry pattern is an under-recognised disorder with a poor morbidity and mortality prognosis. We compared physical activity levels between adults with a restrictive spirometry pattern and with normal spirometry. Methods: Restrictive spirometry pattern was defined as a having post-bronchodilator FEV1 /FVC ≥ Lower Limit of Normal and a FVC<80% predicted in two population-based studies (ECRHS-III and SAPALDIA3). Physical activity was measured using the International Physical Activity Questionnaire. The odds of having low physical activity (<1st study-specific tertile) was evaluated using adjusted logistic regression models. Results: Subjects with a restrictive spirometry pattern (n = 280/4721 in ECRHS, n = 143/3570 in SAPALDIA) reported lower levels of physical activity than those with normal spirometry (median of 1770 vs 2253 MET·min/week in ECRHS, and 3519 vs 3945 MET·min/week in SAPALDIA). Subjects with a restrictive spirometry pattern were more likely to report low physical activity (meta-analysis odds ratio: 1.41 [95%CI 1.07–1.86]) than those with a normal spirometry. Obesity, respiratory symptoms, co-morbidities and previous physical activity levels did not fully explain this finding. Conclusion: Adults with a restrictive spirometry pattern were more likely to report low levels of physical activity than those with normal spirometry. These results highlight the need to identify and act on this understudied but prevalent condition. Highlights: Subjects with a restrictive spirometry pattern had low level of physical activity. Low physical activity was not due to obesity, respiratory symptoms or comorbidities. These results raise awareness about this understudied prevalent condition. Abstract : "Take home" message: This analysis of data from two large population-based studies shows that adults with a restrictive spirometry pattern have low levels of physical activity. This may be one of the reason why higher mortality and morbidity is observed among these subjects.